2014
DOI: 10.1177/0002764214527094
|View full text |Cite
|
Sign up to set email alerts
|

Frequent Contributors Within U.S. Newspaper Comment Forums

Abstract: News organizations' online commenting tools have been touted as a boon for the deliberative process, yet only to the extent that they are used by a diverse group of participants who are civil and who provide information that enriches dialogue. The researchers in this study analyzed the degree to which posts in newspaper forums originated from frequent contributors and the civil and informational characteristics of those contributions. A content analysis of comments (N = 2,237) within forums adjacent to opinion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…Although some studies focus on the share of voice to investigate the potential domination by a few users (Stromer-Galley, 2007), others investigate the diversity of socioeconomic characteristics among participants, such as age, gender, or education (Monnoyer-Smith & Wojcik, 2012). Overall, these studies have found that the diversity in comment sections is low and comparatively few users write a high share of comments (Blom, Carpenter, Bowe, & Lange, 2014;Diakopoulos & Naaman, 2011). Beauvais and Bächtiger (2016), acknowledging that most discussions usually do not meet the high normative standards of inclusiveness, have proposed negotiating conflicting values against the background of different goals of deliberation.…”
Section: Inclusivenessmentioning
confidence: 99%
“…Although some studies focus on the share of voice to investigate the potential domination by a few users (Stromer-Galley, 2007), others investigate the diversity of socioeconomic characteristics among participants, such as age, gender, or education (Monnoyer-Smith & Wojcik, 2012). Overall, these studies have found that the diversity in comment sections is low and comparatively few users write a high share of comments (Blom, Carpenter, Bowe, & Lange, 2014;Diakopoulos & Naaman, 2011). Beauvais and Bächtiger (2016), acknowledging that most discussions usually do not meet the high normative standards of inclusiveness, have proposed negotiating conflicting values against the background of different goals of deliberation.…”
Section: Inclusivenessmentioning
confidence: 99%
“…This has implications for civility and democracy. While disinformation and polemics may stimulate a broader public conversation about social concerns such as gun violence, the relative incivility of these narratives which included insults such as “libtard” are unlikely to increase users’ tolerance to individuals’ championing opposing perspectives—which is an important precursor to consensus-building (Blom et al, 2014; Nisbet and Scheufele, 2004; Sunstein, 2017; Walsh, 2007). Conversely, fact-based narratives, particularly those discussing May’s mental health, could assist in consensus-building regarding health care in America.…”
Section: Resultsmentioning
confidence: 99%
“…In the case of school shootings, correct information could lead to conversation regarding what conditions created a crisis and what interventions might solve the problem. Mis-and-disinformation, in contrast, may simply fuel polemics and incivility on a forum (Blom et al, 2014). While narratives rooted in incorrect information may have utility insofar as they spark conversation about an important issue, they may undermine civility and constructive engagement (Borah, 2014).…”
Section: Opinion Leaders (In)civility and Narrativesmentioning
confidence: 99%
See 1 more Smart Citation
“…Frequent posters, according to Blom et al, are more likely to act in uncivil and less deliberative ways [19]. Additionally, this negativity can snowball, according to Rösner and Krämer, who posit that aggressive comments online only serve to change the understood ground rules of comment sections thus opening the door to a new, more vitriolic dialogue [20].…”
Section: Literature Reviewmentioning
confidence: 99%